SELF-EXTINGUISHING"" CIGARETTE LEGISLATION. (Tufts Archival Research Center, 2007)
Marginalia; Letter from Samuel D. Chilcote Jr. to the Executive Committee regarding legislation passed to form a committee dedicated to determining the feasibility of fire safe cigarettes.